Bics Or Calps? A Study into The Potential Of The Revised Science Curriculum In Developing Basic Interpersonal Communication Skills (Bics) In The Bilingual Learners. - Kularathne, S.A.; Perera, Marie (University of Jaffna, 2014)
It is almost twelve years since Bilingual Education has been reintroduced to the Sri Lankan National curriculum .One of the objectives of this introduction is to improve the English language competency of the student .At the inception only a limited number of schools were involved in this programme. However, the intention was to gradually spread it to all the schools. Yet, even by the year 2013 only 17.5 of the schools in the country have commenced bilingual education. In most countries where bilingual education is implemented Content and Language Integrated Learning (CLIL) helps the bilingual learners. According to the theoretical basis of CLIL, learners need to develop both the Basic Interpersonal Skills (BICS) as well as Cognitive Academic Language Skills (CALPS) develop bilingualism. However, in Sri Lanka such a model is not available. The present study is part of an ongoing study to develop a CLIL model for Sri Lanka. This paper examines the potential of the revised junior secondary Science curriculum in developing social interaction skills such as sharing and negotiating information with peers making use of first language and the second language in accomplishing academic tasks. In this mixed mode study data was gathered through content analysis of revised Science textbooks, classroom observations, and classroom interaction analysis. No rationale has been suggested in the science syllabus to implement the activities given in the text. Majority of the Science teachers lack the pedagogical skills and language competency to focus on the language component of CLIL Even though the English language curriculum has some exploitable content in supporting CLIL as. the language teachers and subject teachers do not work collaboratively in the teaching learning process in Bilingual Education there is not much opportunity to develop the learners BICS. .A workable mechanism should be designed aiming at collaborative partnership between second language teacher and the content teacher.
Keywords: Bi lingual education; English Language teaching; interpersonal communication skills